Academic Senate Minutes 2002-05-09 - Academic Senate:::::::::
One item added to agenda. Agenda and minutes approved. Report from Chair of the Faculty. Recognition of Katie Dunn. Resolution Urging Members Of The California Legislature To Oppose The Legislative Analyst's Recommendation To Take Money From Institutional Aid Programs and Redirect it to The CAL GRANT Program approved. Report from Elizabeth Martinez of International Programs. EMT report resolutions from EPC divided. Item One approved. Item Two referred to SAC. Item Three approved. SAC Resolution Regarding Recruitment approved. FSAC Ranking policy statement postponed to next meeting. No reports.